(untitled) (Medico Legal Update, 2021)
Background: Obesity is caused due to the mismatch between energy intake and expenditure, with food intake more than the requirements leading to an increase in Body mass index (BMI) as a body measurement parameter1 . Parent focused group program is an intervention program where parents are involved in targeting the changes in obesity-related behavior of their obese children. Objectives: To determine the effectiveness of parent-focused group programs on obesity-related behaviors of children aged 6-12 years. Method and Results: The study was conducted in two phases. The first phase included a survey design to identify overweight and obese children from two randomly selected schools as control and experimentalfrom the southern part of Kerala, India. The second phase includedan intervention design with a parent-focused group program for the program’s experimental group, and effectiveness was analyzed from children’s obesity-related behaviors. The key findings indicated that the parent-focused group program was effective in the pre-test and post-test scores of anthropometric measures in the experimental group for both boys and girls. The study suggested that parent-focused programs effectively bring changesin children’s obesityrelated behavior, thus reducing the chances of getting overweight/obese. Conclusion: Parent-focused group interventions are effective as a preventive strategy in reducing obesityrelated behavior among children.